Structure and release properties of pyrethroid/sulfobutyl ether β-cyclodextrin intercalated into layered double hydroxide and layered hydroxide salt - Zhang, Xiaoguang; Liu, Jiexiang; Ren, Jihui (Frontiers in chemistry, 2022)
The aim of this study was to realize the intercalation of the pyrethroid pesticides beta-cypermethrin (BCT) and lambda-cyhalothrin (LCT) into ZnAl-layered double hydroxides (LDH) and NiZn-layered hydroxide salt (LHS). BCT (LCT)/SBECD-LDH and BCT (LCT)/SBECD-LHS hybrids were obtained with the aid of sulfobutyl ether β-cyclodextrin (SBECD) through one step method. The hybrids were characterized by powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and thermogravimetry and differential thermal analysis (TGA/DTA). The hybrids based on LHS had larger basal spacing than those on LDH. The LDH-hybrids prepared in N-methylpyrrolidone (NMP) had larger basal spacing than those in ethanol. These results were discussed in terms of the matrix structure and solvent properties. The supramolecular structure of the hybrid was reasonably proposed. Furthermore, the release properties of BCT (LCT) from the hybrids were investigated and discussed in two media. The release rate in pH = 5.0 was slower than that in pH = 6.8. The accumulated release amount of pesticide in pH = 5.0 was lower than that in pH = 6.8. LHS-hybrids synthesized in ethanol exhibit a sustainable release property. These depend on the inclusion complexes’ arrangement and release medium. The release kinetic processes could be described by pseudo-second order and parabolic diffusion models. The release behavior can be controlled by adjusting the synthesis conditions and the releasing media. This provides the guidance for the application of SBECD and LDH (LHS) in pesticide formulation.